Factors affecting antibiotic appropriateness in uncomplicated urinary tract infections in primary care - Li Yan Ng; Lay Hoon Goh; Stephanie C. C. van der Lubbe; Sky Wei Chee Koh (Scientific Reports)
Abstract Urinary tract infections (UTIs) are commonly treated in primary care. Inappropriate antibiotic prescription promotes treatment failure and antimicrobial resistance. To date, there are no studies to evaluate antibiotic appropriateness in UTIs in Singapore. We assessed antibiotic appropriateness in uncomplicated UTIs (uUTIs) and identified factors influencing appropriate prescribing. An inappropriate prescription was defined as one involving an inaccurate uUTI diagnosis, not in line with the 2023 Ministry of Health Singapore Clinical Guideline on UTI, or both. We conducted a retrospective observational study of uUTIs from January to June 2023, using Point Prevalence Survey methodology, at 7 primary care clinics in Singapore. Factors influencing appropriate prescribing were identified with bivariate analysis and multivariable logistic regression. Among 369 uUTIs, 53.4% had inappropriate antibiotic prescriptions. Amoxicillin/clavulanate was the most prescribed antibiotic (47.2%). Inappropriate antibiotic prescriptions were more likely if patients had an antibiotic drug allergy (OR 2.49, 95% CI [1.29–4.81], p = 0.006) or multiple complaints (OR 1.32, 95% CI [1.09–1.61], p = 0.005). The clinic visited significantly influenced antibiotic appropriateness (p = 0.004). This study can galvanise local authorities to institute targeted interventions, including clinical decision support tools, shared decision making and continuing medical education to improve antibiotic stewardship in primary care.